State Conflicts of Interest: Comparative Governance of Indonesian SOEs and Singaporean GLCs - Marentino Narade (CV. Era Digital Nusantara, 2026)
This article examines structural dissonance in the governance of Indonesian state-owned enterprises following the enactment of Law Number 16 of 2025, which establishes the BPI Danantara superholding. Operating under a doctrinal legal methodology with a functional comparative approach against Temasek Holdings in Singapore, this study investigates the dogmatic conflict between the Business Judgment Rule and public finance law. The findings reveal that the current legislative framework creates a legal illusion of corporate autonomy. The retention of absolute veto rights through the Golden Share perpetuates political agency costs and nullifies the separate legal entity doctrine. Consequently, state corporate executives remain highly vulnerable to criminal liability under corruption laws for pure business losses. This induces a deeply systemic conservative bias. To resolve this institutional prematurity, this study urges the immediate codification of a Lex Specialis Sovereign Wealth Fund that formally ratifies the Santiago Principles, guarantees constitutional insulation, and establishes independent oversight mechanisms.